Re-evaluating basophil count as a hematological indicator for bone density: a subgroup analysis from an East Asian population - Wang, Yu-Li; Huang, Shu-Wei; Hong, Jun-Jie; Wang, Tiffany; Lee, Kuei-Chen; Cheng, Chao-Min (Frontiers in Endocrinology, 2025)
BackgroundWhile traditional risk factors for osteoporosis such as age, sex, and menopause are well-established, emerging evidence suggests that immune cells may also influence bone metabolism. Among them, the role of basophils remains poorly understood. This study investigated the association between peripheral blood basophil count and lumbar spine bone mineral density (BMD) in an East Asian adult population.MethodsA retrospective analysis was conducted on 200 adults undergoing health check-ups and lumbar dual-energy X-ray absorptiometry. Basophil count and other hematologic and biochemical parameters were correlated with lumbar spine T-scores using multivariate regression.ResultsBasophil count showed no significant correlation with T-scores in the overall cohort (r = 0.06, p = 0.4261). However, a weak inverse trend was noted in participants with BMI ≥ 27. In contrast, GPT and creatinine were significantly associated with BMD, with alanine aminotransferase (GPT) emerging as a strong independent predictor (β = 0.61, p < 0.001).ConclusionsBasophil count does not appear to be a reliable biomarker for BMD in the general population. However, findings in the higher-BMI subgroup suggest a potential link that warrants further investigation. GPT may hold greater utility as a surrogate marker for bone health in clinical screening. The present findings also highlight the value of publishing negative results and underscore the need for future research in larger and more diverse cohorts.